Skrining Status Gizi Pada Remaja - Rifkind Malik; Ruhsyahadati Ajisman; Alief Dhuha; Annisa Lidra Maribeth; Rahma Triyana; Muhammad Rizki Saputra (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Non-communicable diseases are one of the causes of disability and death in the world which are often found in developing countries, one of the factors is a change in diet that is high in fat, processed meat, high in salt and sugar but low in fiber. The aim of this social empowerment project is to screen the nutritional status of teenagers. The method is carried out sequentially starting from registration, then continuing with measuring height and weight. The results of this social empowerment project are that the majority are female, the majority are 18 years old and the majority's nutritional status is normal. During this screening, nutritional imbalances were also found to be high, so it is necessary to increase education and outreach regarding good and balanced nutrition to avoid various non-communicable diseases in the future.